2010
DOI: 10.1038/ja.2010.141
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of modular polyketide synthases, with implications for protein design and engineering

Abstract: Attempts at generating novel chemistries by genetically manipulating polyketide synthases (PKSs) usually result in no detectable or poor product yield. Understanding processes that drive the evolution of PKSs might provide a solution to this problem. The synonymous-to-non-synonymous nucleotide substitution ratios across alignments of well-characterized PKS modules were examined using a sliding windows approach. Not surprisingly, the overall substitution ratios showed that PKS modules are generally under strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Further, the overall substitution ratios of the Trichoderma PKS ketoacyl synthase module revealed that it is under strong purifying selection. Similar findings have also been reported for PKS from bacteria (Zucko et al, 2011) and lichenized fungi (Muggia et al, 2008).…”
Section: Discussionsupporting
confidence: 77%
“…Further, the overall substitution ratios of the Trichoderma PKS ketoacyl synthase module revealed that it is under strong purifying selection. Similar findings have also been reported for PKS from bacteria (Zucko et al, 2011) and lichenized fungi (Muggia et al, 2008).…”
Section: Discussionsupporting
confidence: 77%
“…Studies on the natural evolution of modular PKSs suggest that recombination plays a major role [10]. In vitro construction of hybrid PKSs creates unnatural junctions, which may account for the low product yield as there is evidence for strong purifying selection in PKS modules [30], i.e. most variation in amino acid sequence is not tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…BGCs also exhibit high rates of insertions, deletions, duplications and rearrangements [19], often exchanging multi-gene blocks with primary metabolism [31] or other BGCs [19]. Shared loci within functional domains, many of which contribute to metabolite chemistry, are under a wide array of selective pressures both across and within clusters [32]. …”
Section: Evolution Of Biosynthetic Pathwaysmentioning
confidence: 99%